Славяно-турецкое языковое и культурное взаимодействие (на материале хамаилов литовских татар) - Мишкинене, Галина (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
One of the most common genre varieties of literary heritage of Lithuanian Tatars is the chamails. Due to their content, chamails are divided into two groups: prayer’s, intended for imams, and so-called faldjey’s, which besides prayers and descriptions of rituals includes materials on the Muslim chronology, advices on the treatment of diseases with the help of prayers, interpretation of dreams, magic texts. Unbelievable value for researchers represents chamails, in which most of the eastern texts of ritual content and prayers are accompanied by an interlinear translation into Belarusian / Polish language. The translated texts from the manuscript (signature 3246 ar.), stored at the Manuscripts and Rare Book Department of the Scientific Library of Kazan Federal University, and manuscripts (signature No. 869) from the collection of professor A. Muhlinsky, stored at the Library of St. Petersburg University, is going to be the object of the comparative study.